Inhibition of Lipopolysaccharide-Induced Inflammatory Bone Loss by Saikosaponin D is Associated with Regulation of the RANKL/RANK Pathway - Wu X; Zhao K; Fang X; Lu F; Zhang W; Song X; Chen L; Sun J; Chen H (Dove Medical Press, 2021)
Xinhui Wu,1,2,* Kangxian Zhao,1,2,* Xiaoxin Fang,3,4 Feng Lu,3,4 Weikang Zhang,1,2 Xiaoting Song,1,2 Lihua Chen,5 Jiacheng Sun,1,2 Haixiao Chen1,2,4 1Wenzhou Medical University, Wenzhou, People's Republic of China; 2Department of Orthopedics, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Linhai, People's Republic of China; 3Zhejiang University School of Medicine, Hangzhou, People's Republic of China; 4Taizhou Hospital of Zhejiang Province, Zhejiang University, Linhai, People's Republic of China; 5Enze Medical Research Center, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Linhai, People's Republic of China*These authors contributed equally to this workCorrespondence: Haixiao ChenDepartment of Orthopedics, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Linhai, 317000, People's Republic of ChinaEmail drchx@126.comBackground: Osteolytic diseases such as osteoporosis are featured with accelerated osteoclast differentiation and strong bone resorption. Considering the complications and other limitations of current drug treatments, it is necessary to develop a safer and more reliable drug to deal with osteoclast-related diseases. Saikosaponin D (SSD) is the active extract of Bupleurum, which has anti-inflammation, anti-tumor and liver protection functions. However, the role of SSD in regulating the differentiation and function of osteoclasts is not clear.Purpose: To explore whether SSD could prevent osteoclast differentiation and bone resorption induced by M-CSF and RANKL, and further evaluate the potential therapeutic properties of SSD in LPS-induced inflammatory bone loss mouse models.Methods: BMMs were cultured in complete medium stimulated by RANKL with different concentrations of SSD. TRAP staining, bone resorption determination, qRT-PCR, immunofluorescence and Western blotting were performed. A mouse model of LPS-induced calvarial bone loss was established and treated with different doses of SSD. The excised calvaria bones were used for TRAP staining, micro-CT scan and histological analysis.Results: SSD inhibited the formation and bone resorption of osteoclasts induced by RANKL in vitro. SSD suppressed LPS-induced inflammatory bone loss in vivo.Conclusion: SSD inhibited osteoclastogenesis and LPS-induced osteolysis in mice both which served as a new potential agent for the treatment of osteoclast-related conditions.Keywords: saikosaponin D, osteoclastogenesis, NF-κB, MAPKs, PI3K-AKT, therapy